Epidemiology and Clinical Impact of Vancomycin-Resistant Enterococcus at King Abdulaziz University Hospital (2015–2022): Prevalence, Risk Factors, and Mortality - Mokhtar JA; Attallah D; Al-Rabia MW; Alqarni MA; Alkuwaity KK; Almoghrabi Y; Daghistani H; Ismail MA; Sharif AT; Redwan B; Ajabnoor AM; Alharbi OS; et al. (International Journal of General Medicine)
Jawahir A Mokhtar,1– 3 Dalya Attallah,2 Mohammed W Al-Rabia,1 Mona Abdulrahman Alqarni,1 Khalil K Alkuwaity,3,4 Yousef Almoghrabi,5,6 Hussam Daghistani,5,6 Mazen A Ismail,7 Asim T Sharif,7 Bayan Redwan,7 Alyaa M Ajabnoor,8 Ohood S Alharbi,9 Ibrahim Mohammed Abu,10 Wafaa Alhazmi,4 Mohammed Mufrrih,4,11 Ahmad M Sait,4,6 Abdelbagi Alfadil,1,12 Yassir Daghistani,13 Hattan Jamal Momin,14 Karem Ibrahem1,2 1Department of Clinical Microbiology and Immunology, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Clinical Microbiology Laboratory, King Abdulaziz University Hospital, Jeddah, 21589, Saudi Arabia; 3Vaccines and Immunotherapy Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 4Department of Medical Laboratory Sciences, Faculty of Applied Medical Sciences, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 5Department of Clinical Biochemistry, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 6Regenerative Medicine Unit, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 7Department of Medical Education, Faculty of Medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 8Department of pharmacy practice, Faculty of pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 9Department of Microbiology and Parasitology, Faculty of Medicine, Umm Al-Qura University, Makkah, Saudi Arabia; 10Department of Community Medicine, Faculty of medicine, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 11Special Infectious Agents Unit BSL-3, King Fahd Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia; 12Centre of Research Excellence for Drug Research and Pharmaceutical Industries, King Abdulaziz University, Jeddah, Saudi Arabia; 13Department of Medicine, Faculty of Medicine, University of Jeddah, Jeddah, Saudi Arabia; 14Medical Service Center, King Abdulaziz University, Jeddah, 21589, Saudi ArabiaCorrespondence: Karem Ibrahem, Department of Clinical Microbiology and Immunology, Faculty of Medicine, King Abdulaziz University, P.O. Box 80205, Jeddah, 21589, Saudi Arabia, Tel +966562525685, Email kaibrahem@kau.edu.saBackground: Enterococcus faecalis and Enterococcus faecium are part of the human microbiota but pose significant risks in clinical settings due to increasing antimicrobial resistance. Vancomycin-resistant enterococci (VRE) are a growing concern, linked to high morbidity and mortality in hospitalized patients.Aim: This study is the first comprehensive investigation of VRE prevalence and associated risk factors at King Abdulaziz University Hospital (KAUH) from 2015 to 2022.Methods: Clinical samples were collected, and VRE isolates were identified using VRE Card GeneXpert, BioFire PCR, and the VITEK 2 system. Descriptive statistical analysis with Stata version 17 summarized patient characteristics, including demographics, comorbidities, hospital exposure, and laboratory findings. Categorical variables were reported as frequencies/percentages, while continuous variables were expressed as mean ± SD or median [IQR].Results: Among 254 adult patients with VRE infections, the median age was 61 years. The most common comorbidities were diabetes, hypertension, and kidney disease. VRE infections peaked in 2021, with urine cultures being the most frequent source. Most patients had prior antibiotic exposure, particularly to vancomycin and carbapenems. Enterococcus faecium was the predominant species, with the VanA phenotype being most common. Alarmingly, 61.8% of VRE-infected patients died during the study period.Conclusion: These findings underscore the critical need for enhanced infection control measures and antimicrobial stewardship to combat VRE and improve patient outcomes.Keywords: vancomycin-resistant enterococci, AMR, mortality, risk factors, hospital infections